The perceptions of pre-service teachers in Universiti Teknologi Mara (UiTM) towards the implementation of School-Based Assessment (SBA) / Norezhan Md Zawawi - Md Zawawi, Norezhan (2014)
School Based Assessment (SBA) is introduced into to Malaysian education system in 2011. This study focused on the perception of Pre-Service Teachers on the implementation of SBA (SBA). School-based assessment is a process of monitoring, evaluating and implementing plans to address perceived weaknesses and strengths of the school. The purpose of this study is to identify the perception of Pre-Service Teachers towards SBA in terms of the level of understanding, preparedness as well as the perceived needs. Data pertinent to the study was collected using a questionnaire which was adapted from several questionnaires from previous researches. A pilot study was conducted to provide a basis for modification and perfection of the research instrument. The data was analyzed using frequencies, percentages, mean and Pearson Correlation Coefficient. The data collected resulted in a mean of 3.53 for understanding level, 3.10 for preparedness level and 5.02 for the perceived needs of SBA. It was also found that there is a significant relationship between Pre-Service Teachers’ understanding of SBA and the preparedness level. In addition, there is also a significant relationship of the number of SBA related courses attended and the preparedness level of the Pre-Service Teachers. Overall, it emerged that Pre-Service Teachers have a relatively positive perception towards the implementation of SBA. Therefore, the implementation of SBA must be improved in terms of teacher training by providing courses for Pre-Service Teachers to gain knowledge and increase their preparedness to implement SBA in order for it to be more effective. It is recommended that future studies to be conducted with larger sample size, which includes Pre-Service Teachers from all teacher training institutions in Malaysia in order to produce a representative result which will allow generalization to be made to a wider population.